Influence of age on the anthropometric and performance characteristics of high-level youth female soccer players - Emmonds, S.; Till, K.; Redgrave, J.; Murray, E.; Turner, L.; Robinson, C.; Jones, B. (International Journal of Sports Science & Coaching, 2018)
The purpose of this study was to evaluate the anthropometric and performance characteristics of high-level youth female soccer players by annual-age category (Under 10 (U10)-U16). Data were collected from 157 female soccer players (U16, n=46; U14, n=43; U12, n=38; U10, n=30), recruited from three high-level female soccer academies in England. Players completed assessments of anthropometry (height and body mass), isometric mid-thigh pull strength, jump height, aerobic capacity, change of direction (505-left/right) and speed (10 and 30m). Magnitude based-inferences were used to assess for practical significance between consecutive age groups. Height (very likely-most likely), body mass (very likely-most likely), absolute strength (most likely), jump height (likely-very likely) and distance on the YYIRL1 (possibly-most likely) were greater in older players. Both speed and change of direction time were most likely to very likely lower in older players. However, only most likely trivial-possibly trivial differences were observed in relative strength between age groups. Findings suggest that physical characteristics except for relative strength differentiate by age categories. These findings provide comparative data and target reference data for such populations and can be used by coaches and practitioners for player development purposes. Practitioners should be aware that relative strength does not differ between age categories in high-level youth female soccer players.